- #1

- 1,206

- 9

## Homework Statement

[/B]

I'm solving for ##f_1## from ##B(f_{1}.1+1.f_{1})## from ## \frac{\partial}{\partial x}(\frac{\partial}{\partial t}+\frac{\partial^{3}}{\partial x^{3}})f_n=-\frac{1}{2}\sum^{n-1}_{m=1}B(f_{n-m}.f_{m}) ##

where ##B=D_tD_x+D_x^4##, where ##B## is the Bilinear operator.

## Homework Equations

[/B]

(above)

## The Attempt at a Solution

I get ##B(f_{1}.1+1.f_{1})=2f_{1xt}## not ##0!##. Whereas the method gets ##\frac{\partial}{\partial x}(\frac{\partial}{\partial t}+\frac{\partial^{3}}{\partial x^{3}})f_1=0##